Research on the Model, Evolution and Development of Chinese Government Guidance Fund - Zhang Wenwen; Guo Cheng (Journal of Social Science, 2022)
As a "government + market" policy tool, government guidance funds mainly use financial leverage to lead market-based funds to achieve the policy goals of promoting local economic growth and cultivating key industries. The government guidance fund of in China started around 2002, entered a period of rapid growth in 2015, and entered the stage of stock optimization in 2017; the fund management model has shown a positive trend of large-scale and standardized development. The study aims to find out the model, evolution and development of Chinese government guidance fund. The study used qualitative methods with case study approach. The study reveal that in the future, the government guidance fund is gradually improving its system design, giving full play to its guiding attributes, supplementing the shortcomings of China’s capital market fundraising, and promoting the development of the real economy in the real industry.